The Jesuit guide to (almost) everything : a spirituality for real life - Martin, James (New York : Harper Collins, 2010)
A practical, spiritual guidebook based on the life and teachings of St. Ignatius of Loyola shows readers how to manage relationships, money, work, prayer, and decision making, while keeping a sense of humor about life.
The contemplative in action : our way of proceeding.
Keywords: Ignatius, of Loyola, Saint, 1941-1556; Jesuits -- Spiritual life; Spiritual life -- Catholic Church